2021
DOI: 10.1007/s00508-021-01903-1
|View full text |Cite
|
Sign up to set email alerts
|

Increase in testosterone levels is related to a lower risk of conversion of prediabetes to manifest diabetes in prediabetic males

Abstract: Summary Background Testosterone plays an important role in the regulation of glucose metabolism. While earlier studies have shown that it has a protective effect in males, unfavorable effects of testosterone on glucose metabolism have been reported in females; however, whether there is a sex-specific relationship between testosterone and glucose metabolism in patients with prediabetes has not been investigated in detail hitherto. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…The present study found a significant inverse association between insulin and both TT and SHBG, even after adjusting for other variables. This finding is consistent with several cross-sectional studies (Kurniawan et al, 2020;Leutner et al, 2022;Osuna et al, 2006;Pasquali et al, 1995;Phillips et al, 2003) and an 8-year longitudinal study (Oh et al, 2002), which found testosterone concentrations to be inversely associated with insulin concentrations over the duration of the study. Even though insulin is not a clinical condition, elevated insulin concentrations, hyperinsulinemia, may be indicative of IR and the future development of metabolic syndrome (Wilcox, 2005) (Ling et al, 2016) (Sung et al, 2011).…”
Section: Insulinsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study found a significant inverse association between insulin and both TT and SHBG, even after adjusting for other variables. This finding is consistent with several cross-sectional studies (Kurniawan et al, 2020;Leutner et al, 2022;Osuna et al, 2006;Pasquali et al, 1995;Phillips et al, 2003) and an 8-year longitudinal study (Oh et al, 2002), which found testosterone concentrations to be inversely associated with insulin concentrations over the duration of the study. Even though insulin is not a clinical condition, elevated insulin concentrations, hyperinsulinemia, may be indicative of IR and the future development of metabolic syndrome (Wilcox, 2005) (Ling et al, 2016) (Sung et al, 2011).…”
Section: Insulinsupporting
confidence: 92%
“…The present study found a significant inverse association between the 2-hour OGTT results and TT. This result is supported by several studies (Leutner et al, 2022;Wittert et al, 2021). An OGTT predicts insulin sensitivity with reasonable accuracy (Stumvoll et al, 2001) and may assist with the prediction of T2DM development (Hayashi et al, 2013), one of the comorbidities associated with obesity (Golay & Ybarra, 2005).…”
Section: Oral Glucose Tolerance Testsupporting
confidence: 85%
“… 6 , 7 An Austrian study has also recently confirmed a relationship between testosterone and insulin sensitivity and related metabolic indices in prediabetic males. 15 Clearly, therefore, HH predisposes individuals to an insulin-resistant state and testosterone restores insulin sensitivity and can potentially reverse type 2 diabetes and prediabetes. 6 , 15–17 …”
mentioning
confidence: 99%
“… 15 Clearly, therefore, HH predisposes individuals to an insulin-resistant state and testosterone restores insulin sensitivity and can potentially reverse type 2 diabetes and prediabetes. 6 , 15–17 …”
mentioning
confidence: 99%